LBJ [videorecording (DVD)] - Harrelson, Woody; Stahl-David, Michael, 1982-; Jenkins, Richard, 1947-; Pullman, Bill; Leigh, Jennifer Jason, 1962- (Sony Pictures Home Entertainment, 2018)
The story of U.S. President Lyndon Baines Johnson from his young days in West Texas to the White House.